PENERAPAN MODEL NHT DENGAN METODE POLAMATIKA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DAN AKTIVITAS SISWA KELAS III SEKOLAH DASAR - Sukasny; Ririn Andriani Kumala Dewi; Kiki Fatkhiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low level of students’ learning mastery in mathematics, where 55% or 18 out of 33 students had not yet achieved the minimum competency standard. This condition occurred because the learning process was still teacher-centered, using conventional methods such as lectures and practice exercises. To address this issue, the Polamatika method was implemented, emphasizing student-centered learning through the use of shadow boxes and collaborative problem-solving related to everyday life. The purpose of this study was to determine the implementation of the Polamatika method and its effectiveness in improving mathematical problem-solving skills in multiplication and learning activity among third-grade students of UPTD SD Negeri 2 Mundu. The research employed Classroom Action Research (CAR) based on Kurt Lewin’s model, consisting of four stages: planning, implementation, observation, and reflection. The study was conducted in two cycles involving 33 students. The results showed an improvement in both learning mastery and student engagement across cycles. Learning mastery increased from 18 students (55%) in the first cycle to 25 students (80%) in the second cycle, meeting the classical success indicator of 80%. Likewise, students’ learning activity improved from 65.15% (active category) in the first cycle to 75.15% (very active category) in the second cycle. In conclusion, the application of the Student-Centered Learning model through the Polamatika method effectively enhanced students’ mathematical problem-solving abilities in multiplication and increased their learning activity in elementary school.